DUALISME HUKUM NIKAH SIRRI DI INDONESIA DALAM PERSPEKTIF FIQIH INDONESIA (Refleksi 41 Tahun Undang-Undang No. 1 Tahun 1974 tentang Perkawinan) - Amin, Moh (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE DUALISM OF UNREGISTERED MARRIAGE LAW IN INDONESIA IN INDONESIAN FIQH PERSPECTIVE (THE REFLECTION ON 41 YEAR OF LAW NO 1 OF 1974 ON MARRIAGE): This paper examines about the legal dualism of unregistered marriages in this country which doesn’t over 41 years after the enactment of Law No 1 year 1974 about marriage by emphasizing on Indonesia Fiqh approach as the method of the analysis. The result of the study found that the perspective of Indonesian Fiqh is the fulfillment of the first obligation which is the responsibility the obligation to fulfill the obligation of the first pillar and marriage according to the religious requirements as defined in article 2 verse (1) is the fulfillment of the normative- theological aspects. The fulfillment of the obligations of both the obligation is registering the marriages as noted in article 2 verse2 for the compliance of the normative aspects-sociological- juridical. The fulfillment of the obligations of both aspects is the main purpose of Article 2 verse (1) and verse (2) of Law No. 1 of 1974 about Marriage. Thus, the dualism of unregistered marriage in Indonesia basically is resolved. A marriage is a legal action if it fulfills the elements of religion and marriage registration procedures based on the rules that have been specified in the legislation. The first element has the function as the legitimate sign and the second element serves the sign of a legal action which has any legal consequences. Marriage which is not recorded and has no legitimation has not yet obtained legal consequences. The meaning is the unregistered marriage or the marriage which is not recorded will automatically not considered as illegal action in Islamic law, besides the unregistered marriage is also not legal in the applicable law in Indonesia.